2006
DOI: 10.3998/ark.5550190.0006.c24
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of reference lipids and their degradation products by Raman spectroscopy, nuclear magnetic resonance and gas chromatography-mass spectrometry

Abstract: Dedicated to Professor Rosa Lederkremer on her 70th anniversary AbstractThe study of organic residues preserved in objects and materials collected in archaeological sites can provide information on the activities of ancient societies. Degraded animal fats, plant oils, beeswax and plant resins are among the most common organic residues found within ceramic vessels or mixed with inorganic pigments in archaeological pastes. The effects of decay of these organic compounds difficult the direct comparison with moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
3
0
4
Order By: Relevance
“…It has been shown that the C]C bond undergoes oxidation over time which results in the decreased intensity of its Raman band. 12 The weak band at around 3011 cm À1 arises from (]CH) vibrations which has also been shown to disappear in the Raman spectra of aged lipids. 12 It was found that it was only these two peaks that changed over time within the analysed set.…”
Section: Effects Of Ageing On the Raman Spectra Of Lipsticksmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been shown that the C]C bond undergoes oxidation over time which results in the decreased intensity of its Raman band. 12 The weak band at around 3011 cm À1 arises from (]CH) vibrations which has also been shown to disappear in the Raman spectra of aged lipids. 12 It was found that it was only these two peaks that changed over time within the analysed set.…”
Section: Effects Of Ageing On the Raman Spectra Of Lipsticksmentioning
confidence: 96%
“…12 The weak band at around 3011 cm À1 arises from (]CH) vibrations which has also been shown to disappear in the Raman spectra of aged lipids. 12 It was found that it was only these two peaks that changed over time within the analysed set. Therefore it is possible to identify and differentiate between lipstick smears even a year or two years aer the deposition of the smear since a great majority of the peaks remain unchanged.…”
Section: Effects Of Ageing On the Raman Spectra Of Lipsticksmentioning
confidence: 96%
“…Sin embargo, las dificultades asociadas al reconocimiento de los alimentos cocinados en ellas llevaron al desarrollo de numerosos trabajos experimentales diseñados con el fin de reducir la ambigüedad en su identificación (Dudd et al 1998;Eerkens 2005;Evershed et al 2008;Maier et al 2005;Malainey et al 1999). En Argentina, si bien los análisis de ácidos grasos en cerámicas arqueológicas han tenido un importante desarrollo en las últimas décadas (Fernández Sancha et al 2021;Gómez Otero et al 2014;González 2005;Illescas et al 2012;Lantos et al 2020;Paleo et al 2018;Pérez et al 2013;Schuster et al 2020;Stoessel et al 2015; entre otros), los diseños experimentales de cocción de alimentos en contenedores son aún escasos (Frère et al 2010;Lantos et al 2012Lantos et al , 2015Pérez et al 2015).…”
Section: Discusión Y Consideraciones Finalesunclassified
“…However, few of the studies include the application of chromatographic and spectroscopic techniques as a multianalytical approach to extract complementary information. For example, the study of organic residues (degraded animal fats, plant oils, beeswax and plant resins), preserved in objects and materials collected in archaeological sites of South America, was undertaken by Maier et al 300 using GC-MS, NMR, FT-IR and FT-Raman spectroscopy, or their study on the identication of inorganic and organic components in black pigments of rock art from Alero Hornillos 2 (Jujuy, Argentina) by combining total XRF, FT-IR and GC-MS. 301 The materials used to perform mural painting in Macedonia 302 were analysed by coupling GC-MS and Raman analysis with a similar methodology to the one used to characterize the organic and inorganic materials of plasterwork decorations in La Alhambra. 303 The last work of Marte et al used HPLC, Raman microscopy and SEM/EDX to identify the materials employed in the manufacture of the Sibyls from the church of San Pedro Telmo (Argentina).…”
Section: The Multianalytical Approachmentioning
confidence: 99%